Representation of Minorities and Elderly Patients in Multiple Myeloma Clinical Trials. (26th April 2018) - Duma, Narjust; Azam, Tariq; Riaz, Irbaz Bin; Gonzalez‐Velez, Miguel; Ailawadhi, Sikander; Go, Ronald
Abstract: Multiple myeloma (MM) occurs in all races, but the incidence in non‐Hispanic black patients (NHBs) is two to three times higher than in non‐Hispanic white patients (NHWs). We determined the representation of minorities and elderly patients in MM clinical trials. Enrollment data from all therapeutic trials reported in ClinicalTrials.gov from 2000 to 2016 were analyzed. Enrollment fraction (EF) was defined as the number of trial enrollees divided by the 2014 MM prevalence. Participation in MM clinical trials varied significantly across racial and ethnic groups; NHWs were more likely to be enrolled in clinical trials (EF 0.18%) than NHBs (EF 0.06%, p < .0001) and Hispanic patients (EF 0.04%, p < .0001). The median age of trial participants was 62 years, with 7, 956 participants (66%) being less than 65 years of age. Collaborations between investigators, sponsors, and the community are necessary to increase access to clinical trials to our minority and elderly patients. Abstract : Studies have documented underrepresentation of minorities and elderly in oncology clinical trials; however, this issue has not been addressed for some of the most common hematologic malignancies. This article focuses on the representation of minorities and the elderly with multiple myeloma clinical trials over the past 16 years.